Correlates of Intergroup Transfer in Male Grey-cheeked Mangabeys - Olupot, William; Waser, Peter M. (International Journal of Primatology, 2001)
We studied factors influencing intergroup transfer in male mangabeys (Lophocebus albigena) inhabiting 7 social groups in Kibale National Park over a 2-year period. The sample consisted of 40 males including 36 that we captured and marked during the study. Intergroup transfers are movements between groups that culminate in either long-term (dispersal) or short-term (visits) residency by males in the new groups. Both dispersers and visitors had a greater tendency to move into groups that contained higher numbers of estrous females than their prior group. Using averages of weekly group counts, we found a significant positive relationship between the number of estrous females in a group and the number of adult males in a group, but not between the number of nonestrous females and the number of adult males in the 7 study groups. There is no evidence that dispersal events were released by aggression. For a sample of males followed ≥2 mo before emigration, aggression did not increase just before emigration. Results suggest that spatiotemporal availability of estrous females is a major proximate factor influencing intergroup transfer in mangabeys. The results also suggest that dispersing males are more sensitive to relative numbers of estrous females than to measures of female availability such as operational sex ratio, socionomic ratio, and the number of excess females that take into account the potential for male-male competition.
Keywords: Mangabey;s Kibale forest; wintergroup transfer; primate dispersal